DEVELOPING VISUAL LEARNING MEDIA BASED ON MACROMEDIA FLASH 8 FOR LINEAR PROGRAM MATERIAL FOR GRADE XI STUDENTS OF SENIOR HIGH SCHOOL - Nita Wulansari; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2021)
One use of technology in education is to make mathematics learning media based on computer applications. The media can be equipped with animation so that it is more interesting and helps visualize the concept of the material. Such media can be applied to linear program material related to visual elements such as graphic images. This study aims to develop a visual learning media based on Macromedia Flash 8 for linear program material for grade XI students of senior high school and find out the level of eligibility of the media.This research development using the ADDIE model namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were material experts, media experts, and students of SMA Negeri 2 Bantul and SMA Negeri 3 Bantul. Data collection techniques are observation, interviews and questionnaires. The data analysis technique uses qualitative data which is converted into quantitative data using a Likert scale and ideal evaluation criteria table.The product of this research is the visual learning media based on Macromedia Flash 8 for linear program material. The results of the eligibility of learning media based on the calculation of the average score of each aspect of the material, media, and student responses are 4.11, 4.16, and 4.24. So the average score of the three aspects is 4.17 in the good category. Thus, this learning media is appropriate for students.